2004
DOI: 10.1373/clinchem.2003.025098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Controlled Feedback Intervention on Laboratory Test Ordering by Community Physicians

Abstract: Background: Most studies of interventions to reduce laboratory test utilization have occurred in academic hospital settings, used historical controls, or have had short postintervention follow-up. Interventions with the greatest impact use multiple approaches, are repeated regularly, include comparisons with physician peers, and have a personal approach. We determined whether laboratory test utilization by community physicians could be reduced by a multifaceted program of education and feedback. Methods: We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 27 publications
(29 reference statements)
3
40
0
1
Order By: Relevance
“…[29][30][31] However, research suggests that they generally lag behind best practice, are often supported by poor evidence, and GP adherence may be low. [32][33][34] Numerous other, more intensive, interventions, such as tailored education/ feedback, [35][36][37][38] decision support, 39,40 redesign of test-order forms, 41 and physician quality Funding This project was funded by the MRC Methodology Research Panel Grant 'Making diagnostic systematic reviews fit for purpose: improving decision making in the NHS' (Grant Number: G0801405).…”
mentioning
confidence: 99%
“…[29][30][31] However, research suggests that they generally lag behind best practice, are often supported by poor evidence, and GP adherence may be low. [32][33][34] Numerous other, more intensive, interventions, such as tailored education/ feedback, [35][36][37][38] decision support, 39,40 redesign of test-order forms, 41 and physician quality Funding This project was funded by the MRC Methodology Research Panel Grant 'Making diagnostic systematic reviews fit for purpose: improving decision making in the NHS' (Grant Number: G0801405).…”
mentioning
confidence: 99%
“…This is not surprising given that the decision to order a test in an individual patient ultimately rests with the individual doctor. Evidence suggests that doctors with more clinical experience, confidence in their clinical judgment [5,6,22], pride in their work [5], and who do not fear risk taking or uncertainty [1,5,16,22,28] tend to request fewer tests than those who dislike uncertainty and have less experience. Doctor demographics appear to influence test ordering.…”
Section: Doctor-related Factorsmentioning
confidence: 99%
“…Involvement in research, specifically in guideline development, was found to reduce the number of tests requested [10]. Another factor found to reduce test ordering was giving doctors feedback on how their test ordering rates compared to colleagues [8,10,16]. Cognitive biases influence the diagnostic process as a whole, and thus inevitably impact on test ordering [23,24].…”
Section: Doctor-related Factorsmentioning
confidence: 99%
“…Continuous education of medical doctors has been demonstrated as an effective means for decreasing redundant tests ordering in the hospital setting (16) as well as by practicing community physicians (17).…”
mentioning
confidence: 99%